Saturday
March 25, 2017

Post a New Question

Posted by on .

Solve:
3x + 7y + 5= 0
4x - 3y - 8 = 0

Find p; if:
px + y - 1= 0

  • Math - ,

    I.
    3x + 7y + 5 = 0
    4x - 3y - 8 = 0

    To solve, we can either use substitution or elimination method. For substitution, we choose one equation and represent one variable in terms of the other. Let's choose the first equation, and represent x in terms of y:
    3x + 7y + 5 = 0
    3x = -7y - 5
    x = (-7/3)y - 5/3
    then we substitute this to the 2nd equation:
    4x - 3y - 8 = 0
    4[(-7/3)y - 5/3] - 3y - 8 = 0
    (-28/3 y - 20/3 - 3y - 8 = 0)*3
    -28y - 20 - 9y - 24 = 0
    -37y = 44
    y = -44/37
    substituting this back to either equations and solving for x,
    x = 41/37

    II.
    px + y - 1= 0
    px = 1 - y
    p = (1-y)/x

    hope this helps~ :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question